Tissue remodeling during maturation of the Drosophila wing. - Kiger, J.A.; Natzle, J.E.; Kimbrell, D.A.; Paddy, M.R.; Kleinhesselink, K.; Green, M.M. (Developmental Biology, 2007)
The final step in morphogenesis of the adult fly is wing maturation, a process not well understood at the cellular level due to the impermeable and refractive nature of cuticle synthesized some 30 h prior to eclosion from the pupal case. Advances in GFP technology now make it possible to visualize cells using fluorescence after cuticle synthesis is complete. We find that, between eclosion and wing expansion, the epithelia within the folded wing begin to delaminate from the cuticle and that delamination is complete when the wing has fully expanded. After expansion, epithelial cells lose contact with each other, adherens junctions are disrupted, and nuclei become pycnotic. The cells then change shape, elongate, and migrate from the wing into the thorax. During wing maturation, the Timp gene product, tissue inhibitor of metalloproteinases, and probably other components of an extracellular matrix are expressed that bond the dorsal and ventral cuticular surfaces of the wing following migration of the cells. These steps are dissected using the batone and Timp genes and ectopic expression of alphaPS integrin, inhibitors of Armadillo/beta-catenin nuclear activity and baculovirus caspase inhibitor p35. We conclude that an epithelial-mesenchymal transition is responsible for epithelial delamination and dissolution.